2009
DOI: 10.1128/aac.00882-09
|View full text |Cite
|
Sign up to set email alerts
|

Role of Plasmodium falciparum Digestive Vacuole Plasmepsins in the Specificity and Antimalarial Mode of Action of Cysteine and Aspartic Protease Inhibitors

Abstract: Hemoglobin (Hb) degradation is essential for the growth of the intraerythrocytic stages of malarial parasites. This process, which occurs inside an acidic digestive vacuole (DV), is thought to involve the action of four aspartic proteases, termed plasmepsins (PMs). These enzymes have received considerable attention as potential antimalarial drug targets. Leveraging the availability of a set of PM-knockout lines generated in Plasmodium falciparum, we report here that a wide range of previously characterized or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
66
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 59 publications
2
66
2
Order By: Relevance
“…The formation of swollen vacuoles in recPfHly III-transfected parasites may be a result of the following: (i) recPfHly III may be an influx channel and overexpression results in vacuolar swelling; (ii) in addition to channel activity, recPfHly III may have a regulatory effect on proteases and overexpressing recPfHly III may have inhibited these proteases. Prior reports have shown that protease inhibition can cause swollen vacuole phenotypes (35,36). It is quite possible that overexpression of recPfHly III results in the accumulation of metabolic products.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of swollen vacuoles in recPfHly III-transfected parasites may be a result of the following: (i) recPfHly III may be an influx channel and overexpression results in vacuolar swelling; (ii) in addition to channel activity, recPfHly III may have a regulatory effect on proteases and overexpressing recPfHly III may have inhibited these proteases. Prior reports have shown that protease inhibition can cause swollen vacuole phenotypes (35,36). It is quite possible that overexpression of recPfHly III results in the accumulation of metabolic products.…”
Section: Discussionmentioning
confidence: 99%
“…27 Hemoglobin is hydrolyzed by a multiprotein complex containing aminopeptidases, aspartic proteases (plasmepsins), and cysteine proteases (falcipains). 28,29 This degradation of large amounts of hemoglobin is believed to be critical to provide a source of amino acids and to help maintain intracellular osmolarity during rapid parasite growth. 30 However, the breakdown of …”
Section: Discussionmentioning
confidence: 99%
“…4 An analysis of the binding site region of PM II reveals that the binding site regions of PM I, IV, and HAP show 84%, 68% and 39% identity, respectively, while there is a lower degree of identity between the other six PMs. 8 PM V, IX and X have been shown to be produced in intraerythrocytic parasites 1,[10][11][12][13] but to date, function has been elucidated only for PMV.…”
mentioning
confidence: 99%
“…500 million people each year. 1 The disease is caused by parasites from the genus Plasmodium and the Plasmepsins (PMs) are a family of aspartyl proteases (AP) found in each of the five species of Plasmodium that affect humans (P. falciparum, P. vivax, P. malariae, P. ovale and P. knowlesi). This study focuses on the identification of PM inhibitors of the most lethal species, P. falciparum.…”
mentioning
confidence: 99%
See 1 more Smart Citation